Analisis Produk Sisa dalam Menentukan Pendapatan Produksi Utama Usaha Brownies Ranca Khadeejah OS - Misral Misral; Sri Rahmayanti; Dedi Dermawan (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
In the production process, companies incur production costs, such as raw material costs, labor costs, FOH and other manufacturing costs to produce the main product. Where the main product is the main goal of production. However, in the production process of the main product there is unavoidable waste, residue or waste, which is commonly referred to as by-products. The purpose of this research is to analyze the by-product to the selling price of the main product. The analysis was carried out to find out the calculation of the by-products produced by the company, including the principles used. The results of the study show that Ranca Khadeeja Os Cake Business calculates the cost of by-products by adding the cost of the main product which then after the product is sold its income is recognized as other income. In this case the authors suggest that the revenue from the by-product can reduce the cost of the main product so that the selling price becomes cheaper and can increase the company's profit.